Obesity, fitness, and brain integrity in adolescence. (1st October 2015) - Ross, Naima; Yau, Po Lai; Convit, Antonio
Highlights: We examine fitness, insulin resistance, and brain integrity in adolescents. Fitness and insulin resistance correlated with orbitofrontal cortex integrity. Fitness does not predict brain integrity independent of insulin resistance. Fitness correlated significantly with visual working memory but not attention. Physical fitness may play an important role in maintaining brain integrity. Abstract: Objective: We set out to ascertain the relationship between insulin resistance, fitness, and brain structure and function in adolescents. Design and methods: We studied 79 obese and 51 non-obese participants who were recruited from the community, all without type 2 diabetes mellitus. All participants received medical, endocrine, neuropsychological, and MRI evaluations as well as a 6-minute walk test that was used to estimate fitness (maximal oxygen consumption). Results: Obese adolescents had significantly thinner orbitofrontal cortices and performed significantly worse on Visual Working Memory tasks and the Digit Vigilance task. Insulin sensitivity and maximal oxygen consumption (VO2 max) were both highly correlated with central obesity and orbitofrontal cortical thickness, although insulin sensitivity was the stronger predictor for orbitofrontal cortical thickness. We also found that VO2 max was the only significant physiological variable related to visual working memory. Conclusions: This is the first study to report positive associations between insulin resistance, VO2 max, and frontal lobe brain integrity in adolescents. Given the importance of brain health for learning and school performance, we conclude that schools should also emphasize physical fitness in order to maintain structural and functional brain integrity and facilitate academic achievement.